Preliminary Assessment of Flourine Level of Spring and Stream Water in South West Nigeria - Makanjuola, Olakunle Moses (Pakistan Journal of Nutrition, 2012)
Four water samples from each of spring and stream in some locations across South-West, Nigeria, were analyzed for their fluoride levels and some other quality parameters. The samples coded 101, 202, 303, 404 representing spring water and 505, 606, 707, 808 representing stream water were analyzed for fluoride levels using Ion Selective Electrode method (ISE) while other quality parameters such as calcium, chloride, alkalinity, hardness and pH were determined using standard methods. The results obtained showed low fluoride concentrations of 0.15 ppm and 0.03 ppm in samples 101 and 202 respectively (spring water) while other water samples contained no traces of fluoride. These values are far below World Health Organization (WHO) limits of 1.50 ppm fluoride for drinking water. The water contained low calcium and chloride contents, ranging from 20.0 mg/l to 37.5 mg/l (hardness) indicating that the water is soft. pH values of between 5.6 and 6.0 were also obtained in contrast to 6.5-8.5 as stipulated in the World Health Organization guideline (WHO) for drinking water.